Innovative technologies of flour dishes in restaurants - Antonenko, Artem; Stukalska (Ivanova), Nataliia (My University, 2023)
Therefore, the aim of the work is the scientific justification and development of the technology of Polish sauce using avocado oil and the study of its quality. Метою роботи є наукове обґрунтування та розробка технології польського соусу з використанням олії авокадо та дослідження її якості.
Keywords: кафедра технології ресторанної і аюрведичної продукції; nutritional value; функціональні продукти; харчова цінність; харчові волокна; technology; functional products; food fibers; sauces; соуси